Stress and deformation analysis of powerhouse cavern of Rasuwagadhi hydroelectric project, Rasuwa, Central Nepal - N.B K; S. Panthee (Lowland Technology International, 2020)
An underground powerhouse cavern of RasuwagadhiHydroelectric project lies in Bhotekoshi River, northern part ofRasuwa, Central Nepal. Letter box shaped cavern of maximumdimension 76.6 m in length, 15.3 m in width and 39.65 m inheight is situated at the depth of 320 m with its longitudinal axisof east to west. Geologically, the area belongs to the rock of thequartzite with intercalation of dark grey schist of HigherHimalayan succession. To determine different properties unitweight, point load strengths of rock samples were done for themodel analysis. The rock mass properties based on GSI wererecorded in different chainage of cavern. By using variousgeotechnical property, and numerical methods deformationanalysis of cavern was done. The analyses were carried byusing 3-Dimensional and 2-Dimensional numerical modelingfrom Examine3D and Phase2 softwares and then the modelingresult were compared with the instrumented data from multi-pointborehole extensometers. The deformation from both numericalmodel and instrumental data showed similar results